2016
DOI: 10.1371/journal.pone.0155120
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Adipose Tissue Is Associated with Plaque Burden and Composition and Provides Incremental Value for the Prediction of Cardiac Outcome. A Clinical Cardiac Computed Tomography Angiography Study

Abstract: ObjectivesWe sought to investigate the association of epicardial adipose tissue (eCAT) volume with plaque burden, circulating biomarkers and cardiac outcomes in patients with intermediate risk for coronary artery disease (CAD).Methods and Results177 consecutive outpatients at intermediate risk for CAD and completed biomarker analysis including high-sensitive Troponin T (hs-TnT) and hs-CRP underwent 256-slice cardiac computed tomography angiography (CCTA) between June 2008 and October 2011. Patients with lumen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 41 publications
3
16
0
1
Order By: Relevance
“…12,13 Studies revealed that subjects with an increased EAT value evaluated either by CT or cardiac echocardiography exhibit a more FIGURE 1. Epicardial adipose tissue diameter in the two studied groups severe extension of coronary atherosclerosis, and EAT is also related to total plaque load and cardiovascular risk factors, [14][15][16] results confirmed by the present study where patients with MI showed significantly higher volumes of total cholesterol and presented dyslipidemia more frequently than patients with stable angina. In addition, the incidence of MI appears to be directly proportional to the increase in epicardial fat, which is also related to a higher rate of MACE in subjects with known CAD.…”
Section: Discussionsupporting
confidence: 86%
“…12,13 Studies revealed that subjects with an increased EAT value evaluated either by CT or cardiac echocardiography exhibit a more FIGURE 1. Epicardial adipose tissue diameter in the two studied groups severe extension of coronary atherosclerosis, and EAT is also related to total plaque load and cardiovascular risk factors, [14][15][16] results confirmed by the present study where patients with MI showed significantly higher volumes of total cholesterol and presented dyslipidemia more frequently than patients with stable angina. In addition, the incidence of MI appears to be directly proportional to the increase in epicardial fat, which is also related to a higher rate of MACE in subjects with known CAD.…”
Section: Discussionsupporting
confidence: 86%
“…10,11 Subjects with an increased EAT, assessed either by echocardiography or cardiac CT, have a more severe extension of coronary atherosclerosis, and EAT is also linked to the overall plaque burden and cardiovascular risk factors. [12][13][14] Furthermore, the incidence of myocardial infarction seems to be directly proportional to the increase in epicardial fat, which is also related to a higher rate of major adverse cardiovascular events in subjects with known coronary artery disease (CAD). 15,16 Due to its paracrine properties, by secreting serum inflammatory biomarkers EAT brings a significant contribution to the vulnerability of the coronary atheromatous plaque, either by local inflammation or by stimulating neo-angiogenesis and the development of vasa-vasorum and subsequent intra-plaque hemorrhage, plaque rupture and thrombosis.…”
Section: And Acute Coronary Syndromesmentioning
confidence: 99%
“…There have already been some reports about the relationship between EAT and coronary plaque burden based on coronary CT data, 14,15) but there have been none about the association between EAT and coronary plaque burden based on IVUS. EAT is not only a site of energy storage as free fatty acids (FFA), 16) but also acts as a paracrine organ that releases both FFA and vasoactive cytokines directly into the coronary vessels.…”
Section: Discussionmentioning
confidence: 99%